Winterhardiness of some winter wheat (Triticum aestivum), rye (Secale cereale), triticale (x Triticosecale) and winter barley (Hordeum vulgare) cultivars tested at six locations in Finland - Hömmö, Leena; Pulli, Seppo (Agricultural and Food Science, 1993)
The winterhardiness of 24 winter wheat, 13 rye, 5 triticale and 11 winter barley varieties of different origins was tested at six locations in Finland in 1989-1992. The survival ability of the cultivars, their resistance to snow mould (Microdochium nivale) and the correlations between these traits and the growth habit and growth stage were determined. The trials were grouped on the basis of variety ranking, and the differences between the varieties within each group were studied by the analysis of variance. Statistically highly significant differences between varieties were found in all cases. The wintering conditions during the trials were very variable, and this brought about differences in the ranking of cultivars in different trials. In most cases the genotypic-environmental interactions could be explained by the different genetic systems controlling the tolerance to various winter stresses and changes in their intensity.